Determination of chemical fingerprint of RON 95 commercial petrol in Malaysia by chemometric analysis / Rogayah Abu Hassan @ Mohamad - Abu Hassan @ Mohamad, Rogayah (2013)
Arson is one of the most difficult crimes to investigate due to the lack of physical evidence associating a suspect to the crime. In fire investigation, gasoline is the most commonly found because of their volatility, flammability and availability. The importance of this study is to determine the chemical fingerprint of RON 95 petrol for Petronas, Shell and BHP by using chemometric analysis. The research was conducted in two phases. Phase one involved the determination of the chemical fingerprint of RON 95 petrol for three selected brands. While phase two was to determine the composition differences of RON 95 petrol based on the locations of service stations. All samples from 15 service stations were then stored in glass bottle covered with aluminium foil to prevent exposure from light and heat. Hexane was used as a solvent during the extraction of hydrocarbons. Samples were injected into the gas chromatography flame ion detector (GC / FID) for analysis. After getting the data, analysis of chi-square test, principle component analysis (PCA) and QUEST model analysis were conducted. A chi-square test result shows the data obtained are consistent. No positive results were obtained from PCA analysis. QUEST model analysis shows a validity of 93.3%. Chemical fingerprint of RON 95 Petronas was identified at a standard retention time of 5.25 minutes, 6.70, 9.20, 10.25 and 22.95. For RON 95 Shell petrol, the standard retention time was at minute 5.25, 5.60, 6.70, 9.20, 10.25 and 22.95. While for RON 95 BHP was at 5.60, 6.70 and 10.25. All chemical fingerprints were based on the characteristics of the area under the peak.